Multi-omics profiling of calcium-induced human keratinocytes differentiation reveals modulation of unfolded protein response signaling pathways - Anna, M; Mara, M; Artem, S; Eleonora, C; Gerry, M; Lello, Z (Taylor and Francis, 2019)
By proteomic, metabolomic and transcriptomic approaches we shed light on the molecular mechanism by which human keratinocytes undergo to terminal differentiation upon in vitro calcium treatment. Proteomic analysis revealed a selective induction of the ribosomal proteins RSSA, an inhibitor of cell proliferation and inducer of differentiation, HSP 60, a protein folding chaperone and GRP78, an unfolding protein response signal. Additionally, we observed an induction of EF1D, a transcription factor for genes that contain heat-shock responsive elements. Conversely, RAD23, a protein involved in regulating ER-associated protein degradation was down-regulated. All these modifications indicated an ER stress response, which in turn activated the unfolded protein response signaling pathway through ATF4, as confirmed both by the modulation of amino acids metabolism genes, such as XBP1, PDI and GPR78, and by the metabolomic analysis. Finally, we detected a reduction of PDI protein, as confirmed by the increase of oxidized glutathione. Metabolome analysis indicated that glycolysis failed to fuel the Krebs cycle, which continued to decrease during differentiation, at glance with the PPP pathway, allowing NADH production and glutathione reduction. Since unfolded protein response is linked to keratinization, these results may be useful for studying pathological mechanisms as well as potential treatments for different pathological conditions.